Coastal Water Quality Index (CWQI) Assessment of Youtefa Bay, Jayapura: Status and Management Implications - Suhartawan, Bambang; Daawia, Daawia (Media Publikasi Cendekia Indonesia, 2025)
This research aims to assess the water quality status of Youtefa Bay in Jayapura City using the Coastal Water Quality Index (CWQI) method. Youtefa Bay is an important ecological area with mangrove, seagrass, and coral reef ecosystems that currently face anthropogenic pressures. A quantitative approach with descriptive analytical design was conducted through sampling at 12 stations during the dry season (June) and rainy season (November) 2024. Parameters measured included physical aspects (temperature, transparency, turbidity, TSS, salinity), chemical aspects (pH, DO, BOD, COD, nitrate, phosphate, ammonia, heavy metals), and biological aspects (chlorophyll-a, coliform, E. coli, phytoplankton). Results showed that the overall CWQI value for Youtefa Bay was 71.24 (classified as